Febrile Seizure Duration and Temporal Lobe Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs)
Clinical features of febrile seizures and EEG findings were compared in patients who did and did not develop later afebrile seizures among six selected families and 59 family members with febrile convulsions examined at the Department of Clinical Neurological Sciences, University of Western Ontario, London, Ontario.